Dialoguing with Diversity: Towards an inclusive and egalitarian society - Koichi Iwabuchi (Dive-In, 2021)
‘Diversity and inclusion’ has been widely recognized as a key principle to be promoted by institutions, corporations and administrations across the world. Yet actual promotion of diversity does not necessarily enhance egalitarian inclusion of marginalized people. It might operate to manage and/or tame differences in society and foster particular kinds of diversity—business-centered, expedient and pleasurable ones—while suppressing others. Through critical appraisal of the discourse and practice of the promotion of diversity, this paper will discuss several ways in which the apparent embracement of diversity deters the advancement of the tackling of lingering inequality and marginalization with some attention to the Japanese situation. Such critique does not negate the significance of diversity and inclusion, but on-going critical dialogue with diversity is indispensable to positively and productively advance and implement the inclusion of diversity towards the construction of egalitarian inclusive society.